PERANAN SEKTOR–SEKTOR EKONOMI TERHADAP PEREKONOMIAN DI KABUPATEN MINAHASA SELATAN (The Role of Economic Sectors Towards the Economy of South Minahasa District) - Alfian M. Hermanus; Oktavianus Porajouw; Melissa L. G. Tarore (Jurusan Sosial Ekonomi Pertanian, Fakultas Pertanian Universitas Sam Ratulangi, Manado, 2020)
The role of economic sectors in an area is closely related to the role of the government that manages the economy of the region. Government policy in building regional economy is basically to realize the overall welfare of the community in accordance with the wishes and aspirations that develop in the community. The purpose of this study was to determine the role of each economic sector in the economy of South Minahasa Regency. This study started from September to November 2019. Data used in this study were secondary data, in the form of time series data of South Minahasa Regency GRDP from 2014 to 2018 and GRDP of North Sulawesi Province from 2014 to 2018. Data sources were obtained from official publications of Statistics Indonesia of South Minahasa Regency Website and Statistics Indonesia of North Sulawesi Province Website. The method used in this study was the documentation method. Based on the results of the study, it could be concluded that the Agriculture, Forestry and Fisheries Sector played a very important role in the economy of South Minahasa Regency, both in the future and in the current period. However, this also could not be separated from the role of other economic sectors that work together in the formation of the economy of South Minahasa Regency.Keywords: role, economic, sectors, MinahasaSelatan